In Situ Catalytic Pyrolysis of Low-Rank Coal for the Conversion of Heavy Oils into Light Oils - Muhammad Nadeem Amin; Yi Li; Xingmei Lu (Advances in Materials Science and Engineering)
Lighter tars are largely useful in chemical industries but their quantity is quite little. Catalytic cracking is applied to improve the yield of light tars during pyrolysis. Consequently, in situ upgrading technique through a MoS2 catalyst has been explored in this research work. MoS2 catalyst is useful for the conversion of high energy cost into low energy cost. The variations in coal pyrolysis tar without and with catalyst were determined. Meanwhile, the obtained tar was analyzed using simulated distillation gas chromatograph and Elemental Analyzer. Consequently, the catalyst reduced the pitch contents and increased the fraction of light tar from 50 to 60 wt.% in coal pyrolysis tar. MoS2 catalyst increased the liquid yield from 18 to 33 (wt.%, db) and decreased gas yield from 27 to 12 (wt.%, db) compared to coal without catalyst. Moreover, it increased H content and hydrogen-to-carbon ratio by 7.9 and 3.3%, respectively, and reduced the contents of nitrogen, sulphur, and oxygen elements by 8.1%, 15.2%, and 23.9%, respectively, in their produced tars compared to coal without catalyst.